Erkarara Traditional Tradition Viewed from Citizenship Education in Jerol Village, Aru Selatan District, Aru Islands Regency - Lea M. M. Kubela; Fricean Tutuarima; Jumiati Tuharea (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the process of implementing the Erkarara customary tradition in terms of citizenship education in Jerol Village, South Aru District, Aru Islands Regency. how is the Erkarara customary tradition as the civic culture of the Jerol village community. Data collection techniques are used by observation and interviews. The results of this interview show that the traditional erkarara tradition in Jerol village is a tradition that is carried out when there is a new house that the occupants want to occupy. This erkarara customary tradition is a tradition that has existed for a long time and is still maintained today This has become a culture in the Jerol village community. In this tradition there are meanings and sanctions contained in the Erkarara customary tradition, in this tradition there are also cultural values of citizenship, namely social values, togetherness values, religious values and moral values. This value is reflected in the life of the Jerol village community.